Effect Effect of Implementing Safety Recommendation on Outcomes of Patients Receiving Radioiodine Therapy - Hanan Abd El-Razik AbdEl-all, (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2019)
Radiation safety recommendations are an integral part of targeted radionuclide therapy. The current study aimed to assessment of knowledge for patients receiving radioactive iodine therapy, formulate radiation safety recommendations and evaluate the effect of safety recommendations on outcomes of patients receiving radioiodine therapy.Design; Quasi-experimental study was used in this study.Setting: The study was carried out in the Nuclear Medicine Department and Oncology Department at South Egypt Cancer Institute and Assiut University Hospital.Sample: Sample of (30) adult patients from both sex were participated at this study; their ages ranged from (18 – 65) years, having thyroid disorder not pregnant or lactating.Tools: (1) Patient interview assessment questionnaire sheet.Tool (2): Patient knowledge assessment questionnaire sheet (pre/post).Result: There was statistically significant difference between pre and post implementation of safety recommendations as regard total scores of knowledge and patient outcomes.Conclusion: Safety recommendations are effective in improves patient outcomes (minimize radiation hazard and improve knowledge for patients receiving radioiodine therapy. Recommendations: Telenursing strategy application for patients' compliance with radiation safety recommendations after discharge.